KAPASITAS PEMERINTAH DAERAH DALAM KNOWLEDGE CREATION - M.Ed, Drs. Basseng, (Jurnal Desentralisasi, 2010)
Decentralization policy in perspective of knowledge management, particularly in term of knowledge creation is considered unsuccessful. It is not that decentralization policy is not problematic, but inappropriate knowledge utilized by local government in exercising decentralized affairs is indeed problematic.Such knowledge is fall short in enhancing prosperity and quality of democracy at local level, regardless the motivation.